Strategi Layanan Bimbingan dan Konseling di Forum Komunikasi Disabilitas Kudus (FKDK) - Zulfa, Amara (At-Taujih: Jurnal Bimbingan dan Konseling Islam, 2024)
Disability or disability is an Indonesianization of the acronym "differently able people", namely diff-able. The meaning is a person who is capable in different ways. The aim of this research is to determine the strategy for guidance and counseling services at the Kudus Disability Communication Forum (FKDK). Researchers focused on guidance and counseling services by digging deeply into the cases at the research location. This research is descriptive qualitative with a focus based on empowerment strategy theory, namely: basic services, responsive services, and collaborative services. Every human being is born differently, some are normal and some are even abnormal. One of them is disability. Disability itself is a physical and mental disability experienced by a person due to imperfect brain development. As a result, they experience a lot of negative aspects from being ridiculed, ostracized, isolated, insulted, harassed and so on. People with disabilities are also God's creation so in their lives, they have the right to a decent life and work. Therefore, the role of the government is very important in paying more attention to their survival in terms of education, health and so on. Keywords: Strategy, Guidance, Counseling, Disability, Different Ability